Mechanical properties of metallic lithium: from nano to bulk scales. (March 2020) - Fincher, Cole D.; Ojeda, Daniela; Zhang, Yuwei; Pharr, George M.; Pharr, Matt
Highlights: Li metal exhibits a length-scale dependency of its hardness at small scales (43 MPa at 250 nm to 7.5 MPa at 10 μ m). Li metal demonstrates significant strain rate sensitivity to deformation from nano to bulk scales (with stress exponent n  = 6.9 measured from nanoindentation and n  = 6.55 from bulk tensile testing). We discuss the implications of Li's mechanical properties on dendrite formation during cycling of Li metal anodes. Abstract: Despite renewed interest in lithium metal anodes, unstable electrodeposition of Li during operation has obstructed progress in practical battery applications. While deformation mechanics likely play a key role in Li's mechanical stability as an anode material, reports of Li's mechanical properties vary widely, perhaps due to variations in testing procedures. Through bulk tensile testing and nanoindentation, we provide a comprehensive assessment of the strain-rate and length-scale dependent mechanical properties of Li in its most commonly used form: high purity commercial foil. We find that bulk Li exhibits a yield strength between 0.57 and 1.26 MPa for strain rates from 5E-4 s −1 to 5E-1 s −1 . For indentation tests with target   P ˙ / P  = 0.05 s −1, the hardness decreases precipitously from nearly 43 MPa to 7.5 MPa as the indentation depth increases from 250 nm to 10 µm. The plastic properties measured from bulk and nanoindentation testing exhibit strong strain-rate dependencies, with stress exponents of n  = 6.55 and 6.9, respectively. We implement finite element analysis to relate the indentation depth to length scales of relevance in battery applications. Overall, the results presented herein may provide important guidance in designing Li anode architectures and charging conditions to mitigate unstable growth of Li during electrochemical cycling. Graphical abstract: Image, graphical abstract